ALASAN DAN DAMPAK KEBIJAKAN IMPOR BERAS DI INDONESIA - AHADIN HARIO CAESAR NUR, RAHMAT (Jurnal Akuntansi AKUNESA, 2014)
This study aims to analyze the reason Indonesian rice import policy and do what the impact would arise if the government rice import policy. This study used a descriptive approach to thoroughly describe the reasons and impact of rice imports by Indonesia. Sources of data used in this study are from the Central Bureau of Statistics, FAO, and the Regulation of the Minister of Trade of Indonesia. Data collection techniques in this study using a literature study. Results from this study is that although Indonesia is the country's third largest producer of rice, but Indonesia is still not quite able to meet the food needs of its people. In addition to the impact that will arise is that Indonesia will be further away from food security, the impact on farmers in Indonesia, farmers will increasingly cornered by the policy of Indonesia's rice imports. Keywords: rice, imports, policy